Exploring the child-friendliness of high schools in two southern Karnataka districts: a cross sectional study - J., Rakshitha; K. V., Krishnamurthy; Thomas, Jose Jom; Kulkarni, Praveen; Bilimale, Anil S.; M. R., Narayana Murthy (International Journal Of Community Medicine And Public Health, 2020)
Background: Children spend about 8-9 hours per day in schools. Hence, it is important to provide them with good physical, mental and social environment. The wellbeing during the childhood has a potential to provide the strong foundation for a positive health in later adulthood. This study was conducted to assess the child friendliness among the high schools in two districts the southern part of Karnataka. Methods: A cross sectional study was conducted from March 2019 to December 2019 in Mysuru and Chamarajanagara districts of Karnataka. A total of 23 schools were purposively selected for the study. Data was collected using a self-administered, pre structured questionnaire. The data was represented using numbers and percentages and Mann-Whitney U test was used to compare the data of urban and rural schools. Results: The median score of child-friendliness recorded among the high schools in Mysuru and Chamarajanagara districts was 215 with an interquartile range of 198 to 228. The score was out of a maximum score of 248. A median score of 217 (interquartile range: 201-231) and 203.5 (interquartile range: 186.25-226.25) was observed among rural and urban school respectively. Conclusions: The child-friendliness was better in rural schools compared to urban schools with a better participation, enrolment and completion, and community support for education in rural schools. Empowering the students to improve their participation in school planning and other activities, encouraging better enrolment and completion, and involving communities, especially parents in improving the school environment will improve the child-friendliness among urban schools.